Influence of estrogen deficiency on bone around osseointegrated dental implants: An experimental study in the rat jaw model - Giro, Gabriela [UNESP]; Coelho, Paulo G.; Sales-Pessoa, Roberto; Rodrigues Pereira, Rosa Maria; Kawai, Toshihisa; Perez Orrico, Silvana Regina [UNESP] (Elsevier, 2011)
Purpose: The aim of this study was to evaluate the influence of estrogen deficiency on bone around osseointegrated dental implants in a rat jaw model. Materials and Methods: This study used 16 female rats that had the first molars bilaterally extracted and were allowed to heal for 30 days before implant placement. Sixty days after implant placement, the animals were randomly subjected to sham surgery or ovariectomy (OVX). The animals were euthanized 90 days after OVX. Bone-to-implant contact, bone area fraction occupancy between implant threads, mineral density, turnover markers, and cells positive for tartrate-resistant acid phosphatase were assessed for the 2 groups. Results: The results showed that OVX group presented a decrease of systemic bone density, alterations in bone turnover markers, and an increase of cells positive for tartrate-resistant acid phosphatase compared with the sham-surgery group. However, no difference relative to bone-to-implant contact and bone area fraction occupancy was observed between groups. Conclusions: The findings of this study demonstrate that estrogen deficiency may not be considered a risk factor for osseointegrated implant failure in jaw bone. © 2011 American Association of Oral and Maxillofacial Surgeons.